2016
DOI: 10.1038/srep22685
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation mimic of lysine 280 exacerbates human Tau neurotoxicity in vivo

Abstract: Dysfunction and accumulation of the microtubule-associated human Tau (hTau) protein into intraneuronal aggregates is observed in many neurodegenerative disorders including Alzheimer’s disease (AD). Reversible lysine acetylation has recently emerged as a post-translational modification that may play an important role in the modulation of hTau pathology. Acetylated hTau species have been observed within hTau aggregates in human AD brains and multi-acetylation of hTau in vitro regulates its propensity to aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 38 publications
6
56
2
Order By: Relevance
“…Lysine 280 loss facilitates tau self-assembly and exacerbates tau toxicity (Gorsky et al, 2016; Wang and Mandelkow, 2016). …”
Section: Tau Primary Structurementioning
confidence: 99%
“…Lysine 280 loss facilitates tau self-assembly and exacerbates tau toxicity (Gorsky et al, 2016; Wang and Mandelkow, 2016). …”
Section: Tau Primary Structurementioning
confidence: 99%
“…Most MAPT mutations, such as G272V, V337M and R406W and post-translational modifications including acetylation, O-GlcNAc modification and phosphorylation, are located on the carboxyl terminal of tau (Goedert et al, 1998; Spillantini and Goedert, 2000; Mandelkow and Mandelkow, 2012; Yuzwa et al, 2012). Acetylation of K280, which is localized in MTBD, accelerates pathological tau aggregation and increases tau neurotoxicity in vivo (Cohen et al, 2011; Gorsky et al, 2016). Deletion of K280 strikingly enhances the aggregation propensity and cellular toxicity of tau, despite a decrease in the expression of 4R-tau (Khlistunova et al, 2006; Mocanu et al, 2008; Momeni et al, 2009).…”
Section: The Carboxyl Terminal Of Taumentioning
confidence: 99%
“…Interestingly, using the same system, a recent study has shown cellular ablation of adult neuronal structures called mushroom bodies arising during embryonic development suggesting an important role for 4R-Tau during neurodevelopment21. In addition, using a gene switch system to control Tau expression, it was shown that 4R-Tau adult-onset expression does not affect adult life span2223. Thus, while a strong focus has been put on deciphering 4R-Tau toxicity in post-mitotic neuronal cells, it remains unclear whether adult 4R-Tau toxicity requires a neurodevelopmental component.…”
mentioning
confidence: 99%